Freemasonry in the seventh art. An approach to the Spanish case - Serna Galindo, Ricardo (2016)
We have addressed the question of whether there is a Masonic cinema, and we have then focused on the examination of several renown foreign iconic films that we may even have seen and enjoyed, such as The Man Who Would Be King, directed by John Huston. Then we are facing the panorama of Spanish cinema relationship with Freemasonry, by highlighting several films from Spain in which this matter in a more or less clearly displayed. This is the case, amongst other films, of Bearn o La sala de las muñecas _(Bearn or the Dolls’ Room), written and directed by Jaime Chavarri, or El olivar de Atocha, the family saga The Olive Tree of Atocha, directed by Carlos Serrano. In the latter case, Freemasonry and its rituals are cast in interesting passages.